'Smash this sissy boy's mouth, Cuiguo!': Framing and humor in gay Taiwanese YouTubers' self-disclosures about being bullied. Issue 2 (April 2023) - Chen, Li-Chi
Sharing one's past experience of being bullied is expected to be painful, but gay Taiwanese YouTubers' self-disclosures about how they became victims of homophobic bullying are frequently accompanied by humor and shared laughter. Their interactions are also presented multimodally with other visual and audible semiotic resources. Adopting a multimodal social semiotic approach and a framing approach, this study analyzes three YouTube videos about homophobic bullying. Findings suggest that the gay Taiwanese YouTubers frequently shifted between the sociable frame and the audience-targeted frame when interacting with their interactants and audience. They also assumed different narrative roles, serving as the story-teller, the commentator, and the fictionist . How these gay influencers articulate their opinions on behalf of the LGBTQ community also helps them to assert themselves as eloquent, knowledgeable, and humorous sexual moderns.